2020
DOI: 10.1109/tgrs.2020.2979252
|View full text |Cite
|
Sign up to set email alerts
|

Robust CFAR Detector Based on Truncated Statistics for Polarimetric Synthetic Aperture Radar

Abstract: Constant false alarm rate (CFAR) algorithms using local training window are widely used for ship detection with synthetic aperture radar (SAR) imagery. However, when the density of targets is high, such as in busy shipping lines and crowded harbors, the background statistics may be contaminated by the presence of nearby targets in the training window. Recently a robust CFAR detector based on truncated statistics (TS) was proposed. However, the truncation of data in the format of polarimetric covariance matrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Among the many methods of marine ship detection, CFAR is a relatively excellent and commonly used algorithm [34][35][36]. With the development of research, the CFAR algorithm is gradually combined with machine learning methods such as convolutional neural networks and support vector machines, which further optimize the detection results [37][38][39].…”
Section: Two-parameter Constant False Alarm Rate (Tp-cfar) Methodsmentioning
confidence: 99%
“…Among the many methods of marine ship detection, CFAR is a relatively excellent and commonly used algorithm [34][35][36]. With the development of research, the CFAR algorithm is gradually combined with machine learning methods such as convolutional neural networks and support vector machines, which further optimize the detection results [37][38][39].…”
Section: Two-parameter Constant False Alarm Rate (Tp-cfar) Methodsmentioning
confidence: 99%
“…A CFAR framework called fast block CFAR is used [11]. The region of interest (ROI) is divided into equally sized blocks and then the brightest pixels are removed before estimation.…”
Section: Fig 2 Flowchart Of the Npnf Detectormentioning
confidence: 99%
“…The CFAR loss and the FOM are shown in table 1 when the actual PFA is set 1e-5, and the generalized gamma distribution (GГD) is used to model the PNF and the NPNF. The parameter estimation is based on log-cumulants [4] [11]. The ROC curves are also shown in Fig 8 . The result from the ROC curves is in agreement with that from the FOM.…”
Section: Fig 2 Flowchart Of the Npnf Detectormentioning
confidence: 99%
“…It has been proven that polarimetry can provide more information in detecting and classifying targets in SAR images, leading to the wide application of polarimetric SAR (PolSAR) to improve the performances for small ships. A review of detection techniques is presented in [2], and recent advancements are shown in [3].…”
Section: Introductionmentioning
confidence: 99%